Examining the psychometric properties of the Prosocial Behavior Scale Using Indonesian Pesantren (Islamic Boarding Education System) Sample - Syahputra, Wahyu; Widhiastuti, Ika; Baydhowi, Baydhowi; Falah, Saiful; Yundianto, Devie; Ali, Moondore Madalina (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2024)
In the context of behavior, prosocial behavior is needed to maintain individual relationships with others. This behavior has existed among Islamic college students known as Santri. Santri, as an adolescent, has the concept of establishing relationships through prosocial behavior. Therefore, a measuring instrument is needed to determine Santri’s prosocial behavior. The Prosociality Scale is one of the popular instruments in measuring prosocial behavior, and it is essential to adapt and validate the instrument with the characteristics of the Indonesian sample, especially Santri. This study presents evidence of validity and reliability using the Rating Scale Rasch Measurement Model. With a sample of 742, 424 (57.1%) were female and 318 (42.9%) were male. This instrument has met the criteria of good psychometrics according to the Rasch model regarding reliability (0.82 - 0.99) and validity and fulfills the need for measurement invariance.